Measuring the impact of marketing communication on individuals and their attitudes towards the purchase and installation of small solar PV systems in homes in Saudi Arabia - Al Ajmi, Shaima bint Hussein (Journal of Economic, Administrative and Legal Sciences, 2018)
Eyes are directed towards using the solar power to be a main source of power all over the world, especially after the close end of the age of oil and its derivatives. In this research we will get to know how far the marketing communication mechanisms are affecting the individuals and their trends to buy and install the solar power systems at their homes in order to reduce the usage of the fossil fuels and electricity in Saudi Arabia, and encouraging the customers of electricity to adopt electricity generating systems using the solar power. To achieve the goals of this research, the researcher uses the descriptive analytical approach and the questionnaire design instrument and distributing it among the individuals. After that the researcher has collected data and analysed them. The results of the research has elicited the fact that there is a statistical link between the marketing communication tools and the peoples purchasing and installing these systems at their homes. The research has also proved the existence of a relationship of a statistical nature between marketing communication devices and enhancing the information among the people about their purchase of the solar power systems.